DIPLOMASI PUBLIK INDONESIA DI ERA PANDEMI COVID-19 MELALUI BALI DEMOCRACY FORUM TAHUN 2020-2021 - Afeysha Devany, (2023)
This research aims to discuss Indonesia's public diplomacy strategy in the era of the COVID-19 pandemic when conditions became limited through the Bali Democracy Forum in 2020-2021. This research uses the theory of new public diplomacy, digital transition in public diplomacy, and nation-branding. This study uses a descriptive qualitative method with primary and secondary data sources through interviews with the Ministry of Foreign Affairs, related documents, previous research, and articles. This research argues that Indonesia in the pandemic era continues to carry out its public diplomacy by utilizing technological advances as reflected in the 2020-2021 Bali Democracy Forum. Indonesia has entered a further adaptation phase in digitizing public diplomacy through the implementation of this forum. By continuing to carry out this forum in the pandemic era, Indonesia is strengthening its country's nation-brand as a democratic country that takes an active role in finding solutions related to handling the pandemic.